Identification of CRF66_BF, a New HIV-1 Circulating Recombinant Form of South American Origin - Bacqué, Joan; Delgado, Elena; Benito, Sonia; Moreno-Lorenzo, María; Montero, Vanessa; Gil, Horacio; Sánchez, Mónica; Nieto-Toboso, María Carmen; Muñoz, Josefa; Zubero-Sulibarria, Miren Z.; Ugalde, Estíbaliz; García-Bodas, Elena; et al. (Frontiers in Microbiology, 2021)
Circulating recombinant forms (CRFs) are important components of the HIV-1 pandemic. Among 110 reported in the literature, 17 are BF1 intersubtype recombinant, most of which are of South American origin. Among these, all 5 identified in the Southern Cone and neighboring countries, except Brazil, derive from a common recombinant ancestor related to CRF12_BF, which circulates widely in Argentina, as deduced from coincident breakpoints and clustering in phylogenetic trees. In a HIV-1 molecular epidemiological study in Spain, we identified a phylogenetic cluster of 20 samples from 3 separate regions which were of F1 subsubtype, related to the Brazilian strain, in protease-reverse transcriptase (Pr-RT) and of subtype B in integrase. Remarkably, 14 individuals from this cluster (designated BF9) were Paraguayans and only 4 were native Spaniards. HIV-1 transmission was predominantly heterosexual, except for a subcluster of 6 individuals, 5 of which were men who have sex with men. Ten additional database sequences, from Argentina (n=4), Spain (n=3), Paraguay (n=1), Brazil (n=1), and Italy (n=1), branched within the BF9 cluster. To determine whether it represents a new CRF, near full-length genome (NFLG) sequences were obtained for 6 viruses from 3 Spanish regions. Bootscan analyses showed a coincident BF1 recombinant structure, with 5 breakpoints, located in p17gag, integrase, gp120, gp41-rev overlap, and nef, which was identical to that of two BF1 recombinant viruses from Paraguay previously sequenced in NFLGs. Interestingly, none of the breakpoints coincided with those of CRF12_BF. In a maximum likelihood phylogenetic tree, all 8 NFLG sequences grouped in a strongly supported clade segregating from previously identified CRFs and from the CRF12_BF ‘family’ clade. These results allow us to identify a new HIV-1 CRF, designated CRF66_BF. Through a Bayesian coalescent analysis, the most recent common ancestor of CRF66_BF was estimated around 1984 in South America, either in Paraguay or Argentina. Among Pr-RT sequences obtained by us from HIV-1-infected Paraguayans living in Spain, 14 (20.9%) of 67 were of CRF66_BF, suggesting that CRF66_BF may be one of the major HIV-1 genetic forms circulating in Paraguay. CRF66_BF is the first reported non-Brazilian South American HIV-1 CRF_BF unrelated to CRF12_BF